Caracterización de nódulos tiroideos en pacientes de endocrinología del Hospital General Isidro Ayora de la Ciudad de Loja - Rojas Cumbicus, Juan Diego (2020)
Characterization of thyroid nodules in endocrinology patients at the Isidro Ayora General Hospital in the City of Loja Thyroid nodules are a very common pathological entity in the world and in our environment, with an increasing incidence, whose diagnosis and proper follow-up allow to determine the probability of developing malignancy. The purpose of the present study was to determine the incidence of thyroid nodules; establish its type of functionality, TI RADS ultrasound classification and cytological category using the Bethesda system; to determine the ultrasound and functionality criteria that are most likely to develop thyroid cancer, in relation to the result of the cytology obtained by fine needle aspiration puncture (FNA). It was a prospective study, with a quantitative focus and a cross section; developed in a population of 147 patients who attended the Endocrinology service of the Isidro Ayora General Hospital in the city of Loja, treated during 2018. Obtaining as results that female sex predominated in the population studied, the age group from 41 to 65 years was the most affected. Hypothyroidism was the most common diagnosis in the studied group. The TI RADS 3 category prevailed within the radiological classification and the Bethesda II class for cytology, indicative of benignity. The criteria that were associated with greater suspicion of developing malignancy were the diagnosis of hyperthyroidism and subclinical hypothyroidism together with a radiological classification TI RADS IVa or higher. It was concluded that the thyroid function tests and ultrasound determine the use of cytology as a diagnosis of thyroid nodules. Key words: thyroid ultrasound, FNA, hyperthyroidism, subclinical hypothyroidism.